PiRBase: integrating piRNA annotation in all aspects. Issue Volume 50:Issue D1(2022) (6th December 2021) - Wang, Jiajia; Shi, Yirong; Zhou, Honghong; Zhang, Peng; Song, Tingrui; Ying, Zhiye; Yu, Haopeng; Li, Yanyan; Zhao, Yi; Zeng, Xiaoxi; He, Shunmin; Chen, Runsheng
Abstract: Piwi-interacting RNAs are a type of small noncoding RNA that have various functions. piRBase is a manually curated resource focused on assisting piRNA functional analysis. piRBase release v3.0 is committed to providing more comprehensive piRNA related information. The latest release covers >181 million unique piRNA sequences, including 440 datasets from 44 species. More disease-related piRNAs and piRNA targets have been collected and displayed. The regulatory relationships between piRNAs and targets have been visualized. In addition to the reuse and expansion of the content in the previous version, the latest version has additional new content, including gold standard piRNA sets, piRNA clusters, piRNA variants, splicing-junction piRNAs, and piRNA expression data. In addition, the entire web interface has been redesigned to provide a better experience for users. piRBase release v3.0 is free to access, browse, search, and download at http://bigdata.ibp.ac.cn/piRBase .